First Report on the Benthic Invertebrate Community Associated With a Bronze Naval Ram From the First Punic War: A Proxy of Marine Biodiversity - Gravina, Maria Flavia; Casoli, Edoardo; Donnarumma, Luigia; Giampaoletti, Jacopo; Antonelli, Federica; Sacco Perasso, Carlotta; Ricci, Sandra (Frontiers in Marine Science, 2021)
Historical traces of organisms on the seafloor, such as shells and tubes, constitute the ecological memory of ancient benthic assemblages and serve as an an important resource for understanding the assembly of modern communities. Archaeological shipwrecks are particularly interesting submerged substrata for both their archaeological and biological implications. For the first time, we studied the species composition and life-history traits of dominant organisms in the benthic assemblage on a bronze Carthaginian naval ram, which sank more than two thousand years ago in the Southern Tyrrhenian Sea. By comparing the species composition of the ram assemblage with those of the surrounding habitats, we inferred possible colonization patterns for the ram and discussed the informative role of the shipwreck as a proxy of marine biodiversity. The ram assemblage was rich in species, including both sessile (bryozoans, serpulid polychaetes, few bivalves) and motile (gastropods) species. Sexual reproduction with free-spawning fertilization and long-duration larvae characterized most species. The long submersion time of the ram, together with the reproductive strategies, growth forms, and motility of the dominant species were key factors shaping the community of the ram. The ram itself offers an archaeological artifact of inestimable value, but our analysis revealed it to be an effective collector of fauna from the surrounding seabed. The ram community hosted species from a range of nearby natural habitats (mostly coralligenous, detritic bottoms and zoosteracean meadows) and thus served as a proxy for marine biodiversity on the surrounding seabed. We conclude that the presence of many species on the ram that that commonly occur in adjacent habitats of great environmental value was informative and highlight the important marine biodiversity in the area of the Aegadian archipelago.